Implementasi Model Pembelajaran Modified Inquiry pada Konsep Pengenalan Warna Anak Usia Dini - Ifa Aristia Sandra Ekayati , Dwi Imam Efendi (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2019)
Modified inquiry is a learning model by means of lecturers/teachers providing problems to then ask students to formulate and carry out investigations. Modified inquiry is an effort to prevent and identify students misconception, especially in the concept of color recognition. This research was conducted in the 2016 class in science development courses. Data collection techniques in this study use documentation and observation. The instrument used is the learning implementation sheet. Based on the results of instrument validation shows good qualifications from the validators while the results of the trials that have been carried out get very good qualifications. According to the results of the Kruskal-Wallis Test that compares the assessment scores of learning steps by three observes, p-value > (0.05) is 0.226. it can be concluded that there is no significant difference in the assessment of the three observers towards the implementation of the learning steps.